2020
DOI: 10.1089/acu.2020.1436
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned in Teaching Battlefield (Ear) Acupuncture to Emergency Medicine Clinicians

Abstract: Background: Acupuncture, in general, is being proclaimed as an alternative analgesic amid the opioid crisis, and along with this, within emergency departments (EDs) there is a specific interest in a form of ear acupuncture called Battlefield Acupuncture (BFA). It is expected that BFA will be used more widely in emergency medicine as it is easy to learn and can be applied both promptly and easily. Teaching programs will be required to sustain this increased demand and upskill emergency clinicians in this skill.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Moxibustion [ 9 ] and ear acupressing bean therapy [ 10 ] are the treasures of Chinese medicine, and research on moxibustion and ear acupressing bean therapy for vertigo has been in constant development in recent years. Studies [ 11 , 12 ] have shown that stimulating the corresponding response points and acupuncture points in the auricle can help regulate the qi and blood of the internal organs, balance yin and yang, unblock the meridians, and tonify the kidneys and strengthen the spleen, thus achieving a calming and tranquilizing effect and stopping dizziness. In addition, the warmth of the moxibustion fire can be used to stimulate the body, eliminating stagnation, raising the Yang and Qi, and warming the meridians and invigorating the blood, thus promoting the glory of Qi and blood and nourishing the brain, which can effectively suppress vertigo.…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion [ 9 ] and ear acupressing bean therapy [ 10 ] are the treasures of Chinese medicine, and research on moxibustion and ear acupressing bean therapy for vertigo has been in constant development in recent years. Studies [ 11 , 12 ] have shown that stimulating the corresponding response points and acupuncture points in the auricle can help regulate the qi and blood of the internal organs, balance yin and yang, unblock the meridians, and tonify the kidneys and strengthen the spleen, thus achieving a calming and tranquilizing effect and stopping dizziness. In addition, the warmth of the moxibustion fire can be used to stimulate the body, eliminating stagnation, raising the Yang and Qi, and warming the meridians and invigorating the blood, thus promoting the glory of Qi and blood and nourishing the brain, which can effectively suppress vertigo.…”
Section: Introductionmentioning
confidence: 99%